Quality of life of patients undergoing hemodialysis therapy: Integrative review (Research, Society and Development, 2020)
Chronic Renal Insufficiency is a pathophysiological disease with gradual and irretrievable loss of kidney function, whose treatment consists of the filtration of the blood, balancing the concentration of salts and fluids. Due to the degree of invasion of this procedure, the patient is vulnerable to several setbacks, highlighting the need to assess the quality of life of these users. The study is an integrative review of the nursing literature, which aims to analyze the results of scientific work on the quality of life of patients on hemodialysis. Five scientific articles were researched and examined, with the highest number of production in 2017. The articles analyzed pointed out that the categories most affected in the quality of life of these patients are: work restrictions; physical activity and leisure; family support and overload; and nursing actions for patients with double lumen central venous catheters. In these studies, there was a need for investments in nursing research on the theme addressed. In addition, research that highlighted the repercussions on the quality of life of patients in hemodialysis therapy was evidenced, contributing to a better understanding of the assistance provided by the nursing team.